HUBUNGAN NILAI DMF-T TERHADAP PRESTASI BELAJAR ANTARA SDN PAGEJUGAN 01 DENGAN SDN 03 BREBES DI KABUPATEN BREBES - Noviasari Nursasi; Salikun Salikun; Bedjo Santoso; Supriyana Supriyana (Jurnal Kesehatan Gigi, 2015)
TITLEThe relationship of DMF-t index to learning achievement in SDN Pagejugan 01 and SDN 03 Brebes of Brebes DistrictABSTRACTDMF-T score is the grade which is obtained from dental decay, missing and fiiled that caused by dental caries. 89% Indonesian children at the age under 12 years, have dental caries. This condition will effect their health, growth and learning achievement. The aim of the research is to know the relation DMF-T grade to learning achievement between SDN Pagejugan 01 Brebes and SDN 03 Brebes.The type of the research is descriptive quantitative where sample is taken by Proportionate Stratified Random Sampling. There are 209 samples; 119 samples in SDN 03 Brebes and 90 samples in SDN Pagejugan 01 Brebes. The data is taken by observing and examining. The independent variable is DMF-T score and dependent variable is learning achievement.The result of the research is the average DMF-T grade of SDN 03 Brebes is 0,7 which has the lowest criteria and SDN Pagejugan 01 Brebes is 1,4 which has low criteria. The average of learning achievement SDN 03 Brebes is 76,78 which has good criteria and SDN Pagejugan 01 Brebes is 68,46 which has good enough criteria. It means that SDN 03 Brebes tends toward there is relation DMF-T grade to learning achievement and SDN Pagejugan 01 Brebes tends there is no relation to learning achievement. The researcher suggestion is the student should take care of their teeth and mouth by brushing their teeth regularly, teacher and parents should control children’s teeth regularly and they also should introduce how to take care of teeth and mouth. For research, it should be done by using serious caries category like pulpitis or periodontitis. Kew Words  : DMF-T Score, Learning Achievement